2001
DOI: 10.1046/j.1365-2427.2001.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

A proximate cue for oviposition site choice in the bitterling (Rhodeus sericeus)

Abstract: 1. We investigated two possible proximate cues used for oviposition site choice by females of the bitterling (Rhodeus sericeus), a freshwater fish that spawns on the gills of live unionid mussels. The two cues were the flow velocity and/or oxygen content of water emerging from the exhalant siphon of a mussel. 2. Field observations showed that female bitterling always inspected the exhalant siphons of mussels before they spawned in them. Siphon inspection was not always a prelude to spawning and it may serve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 21 publications
2
118
0
Order By: Relevance
“…These two behaviours considerably increase the conspicuousness to males of females that are about to spawn, and may serve as cues to males that a spawning is imminent. Mussel inspection precedes most spawnings and probably serves in assessment of mussel quality (Smith et al 2001). The function of skimming, which involves a female performing a spawning action but without inserting her ovipositor into the mussel gill chamber, is not understood, but is a further conspicuous cue, and possibly a signal, that a female may be about to spawn.…”
Section: Discussionmentioning
confidence: 99%
“…These two behaviours considerably increase the conspicuousness to males of females that are about to spawn, and may serve as cues to males that a spawning is imminent. Mussel inspection precedes most spawnings and probably serves in assessment of mussel quality (Smith et al 2001). The function of skimming, which involves a female performing a spawning action but without inserting her ovipositor into the mussel gill chamber, is not understood, but is a further conspicuous cue, and possibly a signal, that a female may be about to spawn.…”
Section: Discussionmentioning
confidence: 99%
“…In the European bitterling (Rhodeus sericeus), a species of fish that spawns on the gills of freshwater mussels, females use oxygen as a cue to locate mussels in which their eggs will suffer lowest mortalities from suffocation (Smith et al 2000). By sampling the oxygen emerging from the exhalent siphon, the females may detect the suitability of mussels as spawning hosts (Smith et al 2001). Several studies have demonstrated that females prefer to spawn with males that already have egg clutches present in their nest (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The two possible explanations for this difference are that either females lay eggs at a lower density in single-entry than five-entry condos, or males may cannibalize clutches to a greater extent in single-entry condos. There is clear evidence that female fishes are choosy about where they spawn (Itzkowitz & Makie 1986;Gronell 1989;Sikkel 1989Sikkel , 1994Itzkowitz 1991;Knapp et al 1995;Smith et al 2001), and females of some species appear able to distribute a single clutch among several males (e.g. Trexler et al 1997;Jones et al 2001), indicating some control over clutch size.…”
Section: Discussionmentioning
confidence: 99%
“…We also cannot rule out a role for oxygen concentration as a cue, except in the test with artificial mussels, in which oxygen concentration should have been the same in high and low ventilating mussels. Smith et al (2001) suggested that a drop in oxygen concentration between the inhalant and exhalant siphon may be important in the discrimination of bitterling against the least preferred mussel species, A. cygnea. We suggest that mussel ventilation rates and flow speeds are used by female bitterling as important proximate cues in host selection.…”
Section: Discussionmentioning
confidence: 99%
“…The European bitterling has been shown to respond to mussel smell and exhalant water velocity from dummy mussels (Heschl 1989). Smith et al (2001) provided circumstantial evidence that the oxygen content of water emerging from a mussel may be a cue for oviposition site choice. This paper uses host experiments covering a range of potential host properties, including species smell, species shell type and ventilation rate, to determine which host traits govern a female's spawning decision.…”
Section: Introductionmentioning
confidence: 99%